Use of natural rumen modulators to replace monensin plus virginiamycin in high-grain diets for cattle - Araújo, Saulo Alberto do Carmo; Deminicis, Bruno Borges; Rocha, Norberto da Silva; Lourenço, Felippe Meira; Carvalho, Fernanda de Oliveiro (Revista de Ciências Agroveterinárias, 2024)
This study aimed to evaluate food additives for the replacement of monensin and virginiamycin in high-grain diets for cattle. A Latin square experimental design was adopted, represented by four treatments (functional oil, yeast, tannin and control monensin and virginiamycin) in four experimental periods, with four animals cannulated in the rumen. l The natural ruminal modulators fully replaced the ionophores monensin and virginiamycin in the concentrate. Being evaluated: ruminal pH, apparent digestibility and in situ degradability of dry matter. The results showed that the pH variation curve as a function of rumen fluid collection time was not significant (P<0.05) among the additives studied. The additives used to replace monensin and virginiamycin in crossbred cattle fed a diet of 70% concentrate and 30% roughage with fractionation five times a day, are efficient in maintaining rumen pH above 6.0. The additives did not affect digestibility of OM, CP, NDF, FDA and EE. The in situ degradability of the soluble and potentially degradable fractions was higher in the yeast and essential oil treatments, respectively. The additives evaluated are efficient in replacing monensin and virginiamycin.